Testing hadronic interaction models using a highly granular silicon-tungsten calorimeter - Bilki, Burak; Kaplan, Alexander (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2015)
A detailed study of hadronic interactions is presented using data recorded with the highly granular CALICE silicon-tungsten electromagnetic calorimeter. Approximately 350,000 selected π− events at energies between 2 and 10GeV have been studied. The predictions of several physics models available within the GEANT4 simulation tool kit are compared to this data. A reasonable overall description of the data is observed; the Monte Carlo predictions are within 20% of the data, and for many observables much closer. The largest quantitative discrepancies are found in the longitudinal and transverse distributions of reconstructed energy.
Gesehen am 25.05.2020